Natural resources : minerals and mining, mapping and geodetic control - United States Agency for International Development (Washinton DC: United States Agency)
This book derives from an undertaking unique in the history of international cooperation.The purpose was to discuss from the viewpoints of the scientist,the technical specialist, the planner, and the policy maker, the many problems confronting the millions of people whose ways of life are being altered by social, political, and economic change.
aia 28/01/2019
Loans
Keywords: Surveying; Natural Resources; Mines and Mineral Resources